Confessio philosophi: Confessio philosophi - Gradev, Vladimir; Ilić, Danko (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Vladimir Gradev | Владимир Градев Title (English): Confessio philosophi Title (Macedonian): Confessio philosophi Translated by (English to Macedonian): Danko Ilić | Данко Илиќ Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 73-88 Page Count: 15 Citation (English): Vladimir Gradev, “Confessio philosophi,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 73-88. Citation (Macedonian): Владимир Градев, „Confessio philosophi“, превод од англиски Данко Илиќ, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 73-88.